Black Lake along White Pass Trail, ca. 1898 - Curtis, Asahel, 1874-1941 (1898)
Caption on image: 46101. Asahel Curtis. Handwritten on verso: Black Lake, Skagway Trail. PH Coll 519.46107 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number